In1-XGaXN@ZnO: a rationally designed and quantum dot integrated material for water splitting and solar harvesting applications - Rajaambal, Sivaraman; Mapa, Maitri; Gopinath, Chinnakonda S. (Dalton Transactions, 2014)
The highly desirable combination of the visible light absorption properties of In1-xGaxN Quantum dots (QD) along with the multifunctionality of ZnO into a single integrated material was prepared for solar harvesting. This is the first report on InGaN QD integrated with ZnO (InGaN@ZnO), synthesized by a highly reproducible, simple combustion method in 15 min. Structural, microstructural and electronic integration of the nitride and oxide components of InGaN@ZnO was demonstrated by appropriate characterization methods. Self-assembly of InGaN QD is induced in growing nascent zinc oxo nanoclusters taking advantage of the common wurtzite structure and nitrogen incorporation at the expense of oxygen vacancies. Direct integration brings about a single phase structure exhibiting extensive visible tight absorption and high photostability. InGaN@ZnO suggests synergistic operation of tight harvesting and charge conducting components for solar H-2 generation without using any co-catalyst or sacrificial agent, and a promising photocurrent generation at 0 V under visible light illumination. The present study suggests a direct integration of QD with the host matrix and is a potential method to realize the advantages of QDs.